Electric and magnetic properties of titanium-cobalt-oxide single crystals produced by floating zone melting with light heating - Balbashov, A.M.; Mukhin, A.A.; Ivanov, V.Y.; Iskhakova, L.D.; Voronchikhina, M.E. (Физика низких температур, 2017)
Single crystals of spinel Co₂TiO₄, CoTiO₃ of ilmenite structure and pseudobrookite CoTi₂O₅ were grown by means of zone melting equipment URN-2-ZM. The growth processes were performed in an air atmosphere with a speed ∼10 mm/h and a final annealing of the crystal at temperature of 1250 °C. Co₂TiO₄ and CoTi₂O₅ crystals were obtained with a diameter of 12–15 mm and length up to 60 mm, being free of any other phase inclusions and cracks. However, in the CoTiO₃ crystals some controversial features were found: x-ray Laue analysis indicated high-structure perfection while an electronic microscopy revealed small amount of second phase inclusions in contradiction to known phase diagram of this system. Electrical and magnetic properties of grown Co₂TiO₄ and CoTiO₃ single crystals were studied. Semiconducting behavior of the Co₂TiO₄ was established with the energy gap of ∼1.3 eV. No magnetic anisotropy was found in the cubic Co₂TiO₄ single crystals showing a magnetic behavior similar to polycrystals. The rhombohedral CoTiO₃ crystals revealed a magnetic behavior of an easy plane antiferromagnet with a significant anisotropy of the transverse magnetic susceptibilities along and perpendicular to the trigonal c axis.